Linguagem e gramática no aspecto ideológico - VIEIRA, Claudia Correia (2024)
The present work with the "theme and grammar in language ideological aspect: the state school St. Francis of Assisi." Aims to understand the teaching of grammar in English language class in high school. Since the quality of teaching of the Portuguese language has not been very satisfactory in approvals (tender, vestibular, Enem) process, trying to understand this issue, was conducted a field study with the students of 1st year and 2nd year high school, the San Francisco public school, to better understand what are the methods used by the teacher to work with the teaching of grammar in the English language classroom. This work is divided for better understanding of readers into four chapters defined below in addition to an introduction to the subject. In the first chapter discusses language is ideology, which is referred to as the instrument of domination, linguistic, cultural productions, and is a language that allows us to store and transmit information. In the second chapter will be covered grammar, and portraying the difficulties to reproduce the written language to oral language. In the third chapter will address the ideological aspect, will a bordado a division classes related to social, economic and cultural aspect is the role played by the school, and ideologies within this. In the last chapter, the conclusion Labour Organisation field, with results of research that was conducted with middle school students school St. Francis of Assisi, an activity of an essay, analyze the students' productions 1st is the 2nd year, noted that students had problems relating to spelling, cohesion problems, informal registration and agreement. This work is a necessary reflection for the teacher of Portuguese pass to see grammar as something much broader than what traditionally has the grammar in our Portuguese language classes. Show that our communication is text and text can be written and oral. Comparing one to the other, one must show the specificities of each of the symbolic representation using to get to communication.